The N o jump of raindrop spectra - 333086 Waldvogel, A
Raindrop spectra are measured with an electromechanical raindrop spectrometer, responding to drops >0.3 mm in diameter. The radar reflectivity profile is measured simulteneously with a 5-cm vertically pointing radar. Measured raindrop spectra are described by two parameters, N o and A, the intercept and slope respectively of an exponential distribution having the same water content and radar reflectivity factor as the observed sample. Sudden variations in the raindrop spectra and in the reflectivity profile during widespread rain situations were observed. Due to the parameterization used, these sudden variations of the spectra can be recognized easily as N o jumps indicate the transition from one mesoscale area within the precipitation field to another. The characteristics of the N o jumps and the related cloud physics are sdiscussed. An empirical model is proposed for the relation between the type of raindrop spectra and the convective activity of the precipitating air mass.